A comparison of evidence-based medicine practices between primary care physicians in rural and urban primary care settings in Malaysia: a qualitative study - Hisham, Ranita; Liew, Su May; Ng, Chirk Jenn (BMJ Publishing Group, 2018)
OBJECTIVE: This study aimed to compare the evidence-based practices of primary care physicians between those working in rural and in urban primary care settings. RESEARCH DESIGN: Data from two previous qualitative studies, the Front-line Equitable Evidence-based Decision Making in Medicine and Creating, Synthesising and Implementing evidence-based medicine (EBM) in primary care studies, were sorted, arranged, classified and compared with the help of qualitative research software, NVivo V.10. Data categories were interrogated through comparison between and within datasets to identify similarities and differences in rural and urban practices. Themes were then refined by removing or recoding redundant and infrequent nodes into major key themes. PARTICIPANTS: There were 55 primary care physicians who participated in 10 focus group discussions (n=31) and 9 individual physician in-depth interviews. SETTING: The study was conducted across three primary care settings-an academic primary care practice and both private and public health clinics in rural (Pahang) and urban (Selangor and Kuala Lumpur) settings in Malaysia. RESULTS: We identified five major themes that influenced the implementation of EBM according to practice settings, namely, workplace factors, EBM understanding and awareness, work experience and access to specialist placement, availability of resources and patient population. Lack of standardised care is a contributing factor to differences in EBM practice, especially in rural areas. CONCLUSIONS: There were major differences in the practice of EBM between rural and urban primary care settings. These findings could be used by policy-makers, administrators and the physicians themselves to identify strategies to improve EBM practices that are targeted according to workplace settings.